Tingkat Kepatuhan UPN “Veteran” Jawa Timur Terhadap Pelaksanaan Undang-Undang Nomor 25 Tahun 2009 Tentang Pelayanan Publik - Tukiman, Tukiman; Suksmawati, Herlina; Prabowo, Budi (Dinamika Governance : Jurnal Ilmu Administrasi Negara, 2017)
The purpose of this study to see the extent to which the policy UPN "Veteran" East Java as the college of compliance in the application of Law No. 25 Year 2009 on Public Service, Variables used to assess compliance this is to compare the provisions of Law No. 25 in 2009, consisting of service Standards, edict services, Information Systems services Facility Assessment of Human Resources, Means for service users with special needs / disability, Vision, Mission and motto, ISO 9000: 2008, Attribute service Officers, Systems Integrated services , Complaints, method used in this study is a survey research methods that research conducted in the population, but the data is the data studied samples taken from the population and using questionnaires as a data collection tool to obtain a generalization of observations that are not deep. From the level of their explanations of this study used a descriptive approach to evaluation methods. Definition of descriptive research method according Sugiono (2006: 11) is "The research conducted to determine the value of an independent variable, either one or more variables (independent) without making comparisons or connections between variables and the other variables". While Irawan (2004: 49) states that descriptive research is "Research aimed to describe or explain things as they are". Evaluation methods researchers use to judge something by comparing the activity or products with the standards that have been set. The results based on variables and indicators that have been assigned the obtained maximum value / total by 1000 and divided into three (3) zoning compliance with the implementation of Law No. 25 of 2009 on public service, the red zone or low adherence (0-500), yellow zone or moderate adherence (501-800), the green zone or high adherence (801-1000), the National Development University "Veteran" East Java, the total value of  870.14 or green zones or high adherence (801-1000), which needs attention is the unavailability of intimation / appointments services mounted in the bulletin board, not the availability of specific services / disabled, the attributes of service personnel do not use an ID card, and a complaint management is still centralized. Keywords: Compliance, Law No. 25 of 2009 on Public Service, UPN "Veteran" East Java DOI https://doi.org/10.33005/jdg.v7i1.1197